Wearing shades in the bright future of digital media: Limitations of narratives of media power in Egyptian resistance - Wilkins, Karin Gwinn (2012)
"Political engagement means more than reliance on a single medium, but requires collective human action. In making this argument, I consider how the media landscape, along with social and political contexts, have contributed to this process of shifting political power in Egypt. This background contextualizes the limitations of a dominant Hollywood narrative in U.S. media, not only telling a reductive tale of hero, victim and villain, but also privileging the role of social media as an anthropomorphic heroic sidekick. Mediated communication can be valuable as a vehicle for mobilization and as a site for political contestation, but it is the access to the production and reception of knowledge that matters. In essence, the critical issue in political resistance is power, not technology." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-21007